ANALYSIS OF EFFICIENCY AND EFFECTIVENESS OF REGIONAL ORIGINAL INCOME RECEIVING IN THE COVID-19 PANDEMIC AT REGIONAL REVENUE AND ASSETS AGENCY EAST NUSA TENGGARA PROVINCE - Zainudin Adang Djaha; Hapsa Usman; Bernad W. Bowakh (Jurnal Akuntansi Universitas Muhammadiyah Kupang, 2022)
The implications of the COVID-19 pandemic have had an impact on the Regional Revenue and Expenditure Budget (APBD), one of which is regional income through the receipt of regional original income. This is mainly due to the weakening performance of regional original revenues, such as taxes, user fees, and regional wealth management. From the results of the financial statements of the Provincial Government, especially during the COVID-19 Pandemic, namely in 2020, it shows that the realization of the Regional Original Revenue budget has not reached the specified target. Realization of Original Regional Revenue is still fluctuating, namely it is still up and down in the Regional Government Budget of the NTT Province, so it is said to be still unstable. The data analysis technique that the author uses in this paper is descriptive quantitative. The types of data used are qualitative data and quantitative data. Sources of data used are primary data and secondary data. The data was collected by means of observation, interviews, literature study and documentation which will be analyzed using the PAD efficiency ratio and the PAD effectiveness ratio. The results of the study show that the efficiency level of Regional Original Revenue before the COVID-19 Pandemic, namely in 2018 and 2019 was classified as very efficient. In 2018 it was 1.56%, in 2019 it was 1.66%. While the efficiency level of Regional Original Revenue during the COVID-19 Pandemic, namely in 2020 is classified as very efficient with a percentage of 1.71%. The level of effectiveness of local revenue receipts in the period before the COVID-19 pandemic was classified as very effective. In 2018 the percentage was 100.44% and in 2019 the percentage was 97.95%. Meanwhile, during the COVID-19 pandemic, in 2020 the level of effectiveness was classified as less effective with a percentage of 79.59%. This is due to the weakening of economic factors and the large number of tax arrears. Suggestion that can be given to the provincial government of East Nusa Tenggara should continue to strive to increase local revenue by coordinating the collection and supervision of local revenue receipts as well as implementing policies and programs so that the realization of local revenue can achieve the targets set.